Legenda sunt gesta ad sanandas animas: leyes, juicios y actas para la correctio de los Donatistas en Agustín de Hipona - Escribano Paño, María Victoria (2017)
The Donatist crisis forced Augustine to modulate his vision on religious coercion under the influence of changing circumstances. On the one hand, he partook in the appeal for imperial laws to repress Donatus’ partisans. On the other, after the edict of union of 405 and the conference of Carthage of 411, he had to intercede with the civil authorities to moderate the enforcement of the harsh penal clauses prescribed by the laws and he recommended the publication of judicial records (gesta) which contained the confessions of the Donatists as an alternative to the death penalty. Both proposals may have been linked. This paper mainly focuses on Augustine’s epistles 133, 134 and 139 and examines the historical and legislative context where his intercessio before the tribunus et notarius Flavius Marcellinus and the proconsul Africae Apringius took place in 411-412. The article also explores the function of the publication of the judicial protocol as documental evidence of the error and guilt of circumcelliones and Donatists.
Keywords: Agustín, -- Santo, Obispo de Hipona; Procesos; Religión